The cost of sovereign lending in the Middle East after September 11. (23rd February 2007) - Haddad, Mahmoud M.; Hakim, Sam
One of the casualties in the aftermath of the attacks on September 11 has been global confidence in the Middle East. Sovereign risk – the credit risk assessment to the obligations of central governments – is believed to have increased. Using data from JP Morgan, Moody's, S&P, and the World Bank, we explain and quantify the variability of sovereign risk in five MENA countries between 1998 and 2002. Three immediate implications emerge from our results. Our findings help policymakers in MENA countries (1) better understand how financial markets are pricing their risk, (2) identify the specific risk bins which influence their credit spreads, and (3) suggest mitigation techniques on how their sovereign risk can be reduced.